Genus Ziziphus for the treatment of chronic inflammatory diseases - Abdulrhman Alsayari (Elsevier, 2021)
Natural products and traditional medicine are rich sources for developing therapeutics for chronic inflammatory diseases. However, the way from natural products/traditional medicines to Western pharmaceutical practices is not always straightforward. According to the World Health Organization (WHO), chronic diseases are the greatest threat to human health. 3 of 5 people die due to chronic inflammatory disorders worldwide like chronic respiratory diseases, stroke, cardiovascular diseases, cancer, diabetes, and obesity. Various nonsteroidal anti-inflammatory drugs (NSAIDs) are used to reduce inflammation and pain, but there are many side effects of these drugs' administration. Medicinal plants have therapeutic anti-inflammatory effects with low or no side effects. Ziziphus plant species are generally safe and not toxic to humans. Many studies on the Ziziphus species have shown that their therapeutic properties are attributed to the roots, leaves and fruits. Unfortunately, Ziziphus species from different regions worldwide with anti-inflammatory properties have not been documented in a single review paper. Therefore, it is crucial to establish ethnobotanical knowledge and applications of Ziziphus species against chronic inflammatory diseases. The current article exhaustively reviews phytochemical profile, pharmacological studies, toxicological effects, and ethnobotanical uses of Genus Ziziphus in chronic anti-inflammatory diseases. The present review article also highlights the most promising experimental data on Ziziphus extracts and pure compounds active in clinical trials and animal models of chronic inflammatory diseases. This review would be a valuable resource for contemporary researchers in the field to understand the promising role of the Ziziphus genus in chronic inflammatory disorders.